Effect of caffeine on the amplitude of accommodation and pupil size - Vaibhavi V Naik; Mahima Chandra (Wolters Kluwer Medknow Publications, 2023)
PURPOSE: It is a well-known fact that caffeine is an autonomic stimulant, which is said to have a significant effect on visual performance. This study was planned to investigate the effect of caffeine on the amplitude of accommodation and pupil size in adults. MATERIALS AND METHODS: An experimental study was conducted on 54 healthy individuals in the age range of 27-39 years. All the individuals underwent comprehensive eye examinations and were given caffeine through hot coffee (4 mg/kg). Push up method was used to measure accommodative amplitude (AOA) and pupil size was measured using millimeter scale, at baseline (before consuming coffee) and at 20, 40, and 60 min after consumption of coffee. All the measurements were taken on a random eye selected prior to the study. RESULTS: After consumption of caffeine, the AOA and pupil size showed a significant increase (P < 0.001) after 40 and 60 min. AOA elevated from 9.76 standard deviation (SD) ± 1.46D at baseline to 10.79 SD ± 1.55D at 60 min. Similarly, increment in pupil size from 3.53 SD ± 0.77 mm from baseline to 4.20 SD ± 0.77 mm after 60 min was recorded. There was no correlation found between AOA and pupil size at any point of time (r < 0.2). CONCLUSION: AOA and pupil size are affected in adults after caffeine consumption and it is important to take into account the history related to caffeine consumption before ocular and orthoptic evaluation. It can influence and alter the measurements recorded.